O guardião da Constituição: uma análise de qual Poder deve dar a última palavra a respeito da constitucionalidade de leis no Brasil - Batista, Francisco Diego Moreira (2015)
After the appearance and dissemination of democratic rule of law in the world, the Constitution has become a fundamental part in the life of society. The Constitution sets out the authorities with its divisions of functions, it organizes the state, provides the list of fundamental rights, among other relevant duties. Interpreting the Constitution is a central theme of any state with tradition in constitutional jurisdiction. The Constitution’s guardian theme is the basis for the study and definition of the interpretation of its text. Law’s classic theme, was the center of the famous debate between Carl Schmitt and Hans Kelsen, at the end of the first half of the twentieth century. But the debate precedes them, originating since the emergence of the knowledge of Constitution and since the dawn of the judicial review. Currently it is in vogue interesting thesis about institutional dialogue, intending to overcome ancient privilege theories prima facie from one or another power in the interpretation of the Constitution. The institutional dialogue argues that the interpretation is a process in which each power, evolutionarily, gives a contribution to the debate, including the people. After studying the birth of judicial review in the world and the study of three different control systems (United States, France and Austria), it is verified that the display of factors in different countries find different nuances. In Brazil, from an initial use of US doctrine, the country currently adopts a mixture of control with aspects of diffused and concentrated control, which does not clash with most countries intended to be democratic. It is understood that Brazil has a legal system that allows effective institutional dialogue and that our society, with greater daily involvement of the population in public and political debate, paves land on which allow discussions about institutional dialogue of powers as the last word on judicial review. The final prevalent, in Brazil, belongs to the Federal Supreme Court, including parts of a dialogical process between other powers and society.